Impact of Small Industrial Zones on the Economy of Regions (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article examines the importance of small industrial zones in the development of regional economies. Small industrial zones are recognized as an important factor in creating jobs, developing local production, increasing tax revenues, improving regional infrastructure, and strengthening export potential. The economic and social impact of small industrial zones is analyzed using the example of Namangan, and the relevance of supporting their development is substantiated.